Strategies and Challenges in Translating English Idioms Into Indonesian: a Case Study of The Film Up - Laila Qadera Fitria; Otong Setiawan Djauhari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
.This study explores the strategies and challenges involved in translating English idioms into Indonesian, using the animated film Up (2009) as a case study. Idioms often carry cultural meanings that are difficult to render directly, especially in audiovisual media such as subtitles, which face spatial and temporal constraints. This research analyzes ten idioms from the film along with their Indonesian translations, identifying three main strategies applied by the translator: paraphrasing, literal translation, and substitution with equivalent idioms. The findings indicate that paraphrasing is the most frequently employed technique, effectively retaining meaning and ensuring clarity for the target audience. However, some idioms lose their original nuance or emotional impact when translated literally. This research emphasizes the crucial role of cultural sensitivity and contextual awareness in translating idioms, especially in subtitling, where clarity and naturalness of language are essential due to space and time limitations.